2014
DOI: 10.3389/fmicb.2014.00244
|View full text |Cite
|
Sign up to set email alerts
|

Ecological functions of zoosporic hyperparasites

Abstract: Zoosporic parasites have received increased attention during the last years, but it is still largely unnoted that these parasites can themselves be infected by hyperparasites. Some members of the Chytridiomycota, Blastocladiomycota, Cryptomycota, Hyphochytriomycota, Labyrinthulomycota, Oomycota, and Phytomyxea are hyperparasites of zoosporic hosts. Because of sometimes complex tripartite interactions between hyperparasite, their parasite-host, and the primary host, hyperparasites can be difficult to detect and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 93 publications
(124 reference statements)
0
50
0
2
Order By: Relevance
“…Furthermore, the results of mantel test also showed that the photosynthetic and nonpigmented groups were significantly correlated in both lakes ( P = 0.001 in both lakes). Therefore, we hypothesizes that the broad diversity of nonpigmented eukaryotes unveiled in the sorted samples also implied a potential diversity of ecological functional interactions and highlighted their importance among the smallest eukaryotic community, particularly, the recently widely researched parasitism (Lefevre et al ., ; Lepère et al ., ; Sime‐Ngando and Niquil, ; Dunne et al ., ; Gleason et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the results of mantel test also showed that the photosynthetic and nonpigmented groups were significantly correlated in both lakes ( P = 0.001 in both lakes). Therefore, we hypothesizes that the broad diversity of nonpigmented eukaryotes unveiled in the sorted samples also implied a potential diversity of ecological functional interactions and highlighted their importance among the smallest eukaryotic community, particularly, the recently widely researched parasitism (Lefevre et al ., ; Lepère et al ., ; Sime‐Ngando and Niquil, ; Dunne et al ., ; Gleason et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Still, at this level of taxonomic identification and the lack of any knowledge of their ecology does not allow us to make any further hypothesis about their role. For example, many members of zoosporic fungi are hyperparasites having complex tripartite interactions and are consequently difficult to monitor (Gleason et al, 2014). Among Fungi, Chytridiomycota gain more and more attention since a large number of phytoplankton and invertebrate taxa are affected by chytrid parasites.…”
Section: Bolidomonas Pacifica (98%) [Ocean Waters]mentioning
confidence: 99%
“…This paper aims to synthesize novel notions stressing the biological relevance of phytoplankton chytridiomycosis, keeping a focus on the immediate research needs. Our intent is not to recreate existing reviews on the topic (Ibelings et al ., ; Gleason et al ., ; Sime‐Ngando, ; Kagami et al ., ; Gerphagnon et al ., ; Jephcott et al ., ). Rather, we aim to (i) briefly highlight the profound and multifaceted impact of chytrid parasitism on phytoplankton dynamics, (ii) identify the current major gaps in knowledge and (iii) propose future directions to bridge them.…”
Section: Introductionmentioning
confidence: 99%